Primary Results of Our Protocol for Standardization of Perioperative Antiplatelet Agent Management on the Incidence of Epidural Hematoma and Thrombotic Complications in Posterior Cervical Surgery: A Prospective Cohort Study - Gentaro Kumagai; Kanichiro Wada; Toru Asari; Yoshiro Nitobe; Kotaro Aburakawa; Yasuyuki Ishibashi (Spine Surgery and Related Research)
Introduction: This study aimed to standardize perioperative interruption of antiplatelet agents in patients undergoing cervical spinal surgery and investigate the incidence of epidural hematoma and thrombotic complications. Methods: A total of 153 patients, consisting of 85 men and 68 women, were included in this study. Their mean age was 65.5 years. They were divided into two groups: Groups A and B. Group A (139 patients) did not receive preoperative antiplatelet agents, and Group B (14 patients) resumed antiplatelet agents from 7 or 14 days presurgery to 3 days postsurgery. Our analysis encompassed demographic data before surgery, postoperative magnetic resonance image-based assessment of radiological epidural hematoma (EH), and complications such as symptomatic hematoma, blood transfusion, stroke, and venous thromboembolism after surgery. Results: The frequency of medical conditions, such as hypertension, diabetes, and hyperlipidemia, was significantly higher in Group B than in Group A. The CHADS2 scores, which serve as a clinical prediction rule for estimating stroke risk, were significantly higher in Group B than in Group A. In contrast, the intraoperative blood loss was significantly lower in Group B than in Group A. There was no significant difference in radiologically severe EH, hemorrhage, and thrombotic complications between the two groups. Interestingly, none of the patients in Group B had hemorrhagic and thrombotic complications. Conclusions: Our standardized perioperative management of antiplatelet agents did not affect the incidence of radiological EH, hemorrhage, and thrombotic complications in patients undergoing cervical spinal surgery.